(3GdfUjMI GdcGajI def NUg Gddg JYGdi HGdYGajIs - (3CMeO Hf RQhb GdaGSj, RQhb,J (B899 (3g` s ((3GdLGeY GdCRgQ (B_ (3GdbGgQI GdeMQhSI s)
(3ChdgG (B:s
(3GdMeO ddg Ydi efg GdESdGe CeG HYO aGdfUjMI ef GdEjeGf hGdJMbjb jHOC ef YdGeI s
(3BNQgG (B:s
(3Gddge EfG fJhSd Edjc HfYe hMSHfG Gddg hfYe Gdhcjd hGddg JYGdi CYde JeJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B_ (3GdeZQH (B(364 d) s
Keywords: (3GdeLGejYs